Bagaimana Pola Komunikasi Keluarga Minangkabau Mempengaruhi Pelestarian Budaya dan Pengikisan Budaya? - Dwi Rini Sovia Firdaus (Institut Pertanian Bogor, 2020)
This article aims to find a shift in Minangkabau culture that began from a family environment. This article studied four types of Minangkabau families with children aged 10-19 years. This study applied descriptive qualitative research methods with in-depth interview techniques. The SPEAKING model of Hymes was used to construct communication patterns within the family when passing down Minangkabau’s norms through storytelling to children. Norms that do not resemble Minangkabau cultural teachings were taught by families with Minang fathers, while families with non-Minang fathers taught norms that were similar to Minangkabau cultural teachings. This family always taught the value of survival and common sense due their status as migrants. In fact, this is the core value instilled by the ancestors of the Minangkabau people that was misunderstood by their younger generations. The meaning of survival and common sense value introduced by Minangkabau cultural teachings need to be clarified to children through their family environment, so that they can be closer to their own cultural roots. This condition makes them keen to build their own region equipped with positive values learned from the Minangkabau culture.